Growth in Switzerland : Can Better Growth Be Sustained? - Gagales, Anastassios (IMF Working Papers; Working Paper ;, 2002)
Swiss growth performance in the past quarter century has been mediocre. The paper finds that conditional income convergence contributes significantly to slow growth and the poor performance of the domestically oriented sectors has been a drag on growth. However, slow growth is not inescapable. Faster growth would require raising total factor productivity growth, which remains low by international standards, and the investment rate. Further progress in structural reform could sustain the underlying growth rate at about 2 percent in the next few years.